Analisis Pengaruh Penggunaan Media Baru Terhadap Pola Interaksi Sosial Anak Zaman Millenial Di Madrasah Ibtidaiyah Sunan Kalijogo Kota Mojokerto - Amamiyatul Amali; Jiemly Mohammad Luay (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2019)
This study aims to analyze and describe the use of digital media by millennial children, patterns of social interaction of children, and the effect of the use of new media on children's sociability in MI Sunan Kalijogo Mojokerto City. This type of research is an explanatory causal correlation with the survey method using the main instrument of the questionnaire. The population is children of 8-12 years old students of Madrasah Ibtidaiyah Sunan Kalijogo, totaling 123 students. The number of samples were 80 students. The results showed that the level of new media usage among millennials aged 8–12 years in MI Sunan Kalijogo was in the moderate category (1.89) and the social interaction was in the high category (2.45). Assumptions that state that the higher the use of new media, the social interaction of children will tend to be lower can be accepted with a correlation coefficient of 0.54 at a degree of freedom of 0.05 or a 95% confidence level.